Fenomena Geografis Makna Toponimi di Kota Makassar - Tamrin, Tamrin; Haliq, Abdul (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
Geographical Phenomenon of Toponymy Meaning in Makassar City. This study aims to describe the toponymy and naming aspects of the origin of the name of the earth in Makassar City and its surroundings based on the description of the origin of the name. This research uses qualitative descriptive methods with observation techniques, interviews, documentation, and literature review. The data will be analyzed by classifying as a whole. The stages carried out are classifying the names of the earth's appearance in the form of village names, village names, and sub-district names in the Makassar City area and its surroundings. The results of the analysis show that the naming of toponymy (the name of the earth) in Makassar City means embodiment and community. The aspect of embodiment is naming based on plants, animals, terrain, and naming based on the form of natural objects. Furthermore, naming based on social aspects, namely naming based on the form of activities, character names, and naming based on expectations.